2006
DOI: 10.1117/1.2360257
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the dynamics of water in the macrostructural dentine

Abstract: The purpose of this study was twofold: (1) to investigate the nature and degree of water loss at 21 degrees C, 60% relative humidity (dehydration) and at 105 degrees C (desiccation), and to relate these findings with (2) the strains produced in the dentine structure during dehydration and rehydration processes. In stage 1, digital moire interferometry (DMI) was used to study the strain distribution pattern during dehydration and rehydration at 21 degrees C. In stage 2, the nature and degree of water loss was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
(30 reference statements)
2
23
0
Order By: Relevance
“…During experiments specimens were placed in a very stable, specially designed jig. DMI has been used in previous studies to characterize and investigate the biomechanical properties of dental hard tissues (11,12). Heat stimuli were applied by using heated gutta-percha sticks (z135 C), and cold stimuli were applied by using refrigerant spray on a cotton pellet (z-50 C) in the middle third of the labial surface of the crown (6,13).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During experiments specimens were placed in a very stable, specially designed jig. DMI has been used in previous studies to characterize and investigate the biomechanical properties of dental hard tissues (11,12). Heat stimuli were applied by using heated gutta-percha sticks (z135 C), and cold stimuli were applied by using refrigerant spray on a cotton pellet (z-50 C) in the middle third of the labial surface of the crown (6,13).…”
Section: Methodsmentioning
confidence: 99%
“…The level of hydration, in particular the free water, has been shown to influence the mechanical stress-strain behavior of dentin (12). It was also shown that the free water is lost rapidly within the first 2 hours of exposure to room conditions as a result of evaporation from the dentinal tubules and dentin surface (11). These findings suggest that care should be exercised during sample preparation and while comparing findings from different studies.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…During the convection of fully mineralized tissues in air, the free water is lost rapidly and the strains are small, generally < 1% [17] . Therefore, quantifying dehydration shrinkage in hydrated and highly mineralized tissues requires an approach with adequate measurement resolution, which can not be hindered by the moisture changes.…”
Section: Introductionmentioning
confidence: 99%